A multifunctional, plug-and-play and low-cost microfluidic connector system based on electronics standard. Issue 118 (13th November 2015) - Zhao, S. K.; Chen, R.; Yu, Y.; He, L.; Liu, J. Q.; Chen, X.; Qin, S. Y.
Abstract : In this study, we utilized the electrical engineering standard of a 2.54 mm pin-header connector to create two standard microfluidic connectors and two accessories for different applications. Abstract : A reliable, low-cost and standardized microfluidic interface to the outside world is still a challenge for microfluidics. In this study, we utilized the electrical engineering standard a 2.54 mm pin-header connector to create a standard pin-header microfluidic connector (SPHMC) for PDMS based microfluidic devices. This connector is fabricated using universally available pin-header connectors and heat shrink tubing, thus its cost is less than 10 cents per unit. The density of the SPHMC is relatively high (ten fluidic I/O for 63.5 mm 2 ) and the connector can tolerate at least 30 psi, which is beyond the requirement of most microfluidic applications. Moreover, to resolve the issues about small volume injection and bubble removing, we modified the SPHMC and developed several new connectors and accessories. We demonstrate that our connectors and accessories can be used for parallel droplet generation, injection of rare samples and capture of circulating tumor cells.